Akseptabilitas Perawi Syiah dalam Sanad Riwayat Sunni: Analisis Riwayat Aban Ibn Taghlib dalam Kutūb al-Sittah - Mahdi, Fahrizal (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This research discusses the acceptability of the shia theology rawi in the Sunni tradition. Shia rawi narrated many ḥadīth in the main books of sunni ḥadīth and ḥadīth critics often give the a jarḥ so that their narrations are judged as da’if. Aban ibn Taglib is one of the Shia rawi who narrated the ḥadīth in al-Kutūb al-Sittah except in Ṣaḥīḥ al-Bukhārī. He has 5 ḥadīth in all those ḥadīth books and all of the are considered authentic ḥadīths except for only one ḥadīth in Sunan Abu Dawud. Therefore, the research concludes that Shia rawi can accept their riwayah as long as they meet the requirement for the validity of the ḥadīth and are not among the extreme shia who disbelieve and insult the companions of the prophet Muḥammad.